PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN PADA KANTOR PUSAT BANK PEMBANGUNAN DAERAH NTT - Cindy Claudia F M Djara; Rolland E Fanggidae; Ni Putu Nursiani (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This research was conducted at the Head Office of PT. NTT Regional Development Bank. Thepurpose of this study was to determine the effect of Emotional Intelligence and Spiritual Intelligenceon Student Performance at the Head Office of PT. NTT Regional Development Bank. The dataanalysis technique used in this study is by conducting multiple regression tests. The results of thisstudy partially Emotional Intelligence has a positive and significant influence on employeeperformance at the Head Office of PT. The NTT Regional Development Bank and SpiritualIntelligence has not significant influence on employee performance at the Head Office of PT. NTTRegional Development Bank. Simultaneously Emotional Intelligence and Spiritual Intelligencehave a positive but significant influence on employee performance at the Head Office of PT. NTTRegional Development Bank. Emotional intelligence and spiritual influence, employee performancebut small. contributionTherefore the need to pay attention to management factors that can affectother dissimilar employee performance Keywords: Emotional Intelligence, Spiritual Intelligence and Performance